Female athletes' perceptions of a coach's speeches - Breakey, C.; Jones, M.; Cunningham, C. T.; Holt, N. (International Journal of Sports Science and Coaching, 2009)
The purpose of this case study was to examine female athletes' positive and negative perceptions of their coach's pre-game and intermission speeches. Members (n = 20) of a highly successful university women's hockey team were interviewed following two home stands. Researchers transcribed interviews verbatim and conducted an inductive content analysis. Positive features of the speeches were when the coach displayed genuine emotion, spoke in a short and meaningful way, and referred to a set of team values. Participants negatively perceived long and poorly timed speeches, instances when they disagreed with the coach, and when the coach omitted expected information or provided a new unexpected approach. Athletes consistently reported more positive perceptions of speeches than negative perceptions. In summary, the content (e.g., referring to team values) and the delivery (e.g., displaying genuine emotion) of speeches appeared to be closely connected.